(untitled) (International Journal of Engineering and Computer Science, 2024)
We can see people clicking picture and putting efforts to store them. But with time pictures get damaged. To recover pictures from those damages like scratches, graphics image inpainting technique can be used. Image inpainting technique either completes or removes the missing region in images. It’s one among the highly challenging topic in image processing area. Image inpainting techniques are divided into traditional techniques and deep learning techniques. It starts with introduction, types of image inpainting, literature review, discussion and the conclusion.